Pengembangan Pendidikan Tinggi Melalui Budaya Learning Organization Era Society 5.0 - Asih Puji Hastuti (At Turots: Jurnal Pendidikan Islam, 2021)
Entering the era of society 5.0, organizations, especially universities, must immediately choose new breakthroughs related to innovation in all aspects, both in terms of information technology (IT), operational methods, work systems, performance appraisals, virtual team work, virtual leadership and others. Higher education development is absolutely necessary if the organization wants to survive and be able to compete with its competitors. It is important to have a learning organization culture so that organizations are able to adapt to change as a means of learning and continue to improve themselves in a sustainable manner. This article aims to discuss organizational development strategies, especially higher education using the concept of learning organization in order to face the era of society 5.0. The results of this study indicate that innovation is the main key so that higher education is able to change the mechanism it has through a learning organization culture to create technology-based education services.